If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(v + -6) + -2v = 3(-10 + -5v) Reorder the terms: -7(-6 + v) + -2v = 3(-10 + -5v) (-6 * -7 + v * -7) + -2v = 3(-10 + -5v) (42 + -7v) + -2v = 3(-10 + -5v) Combine like terms: -7v + -2v = -9v 42 + -9v = 3(-10 + -5v) 42 + -9v = (-10 * 3 + -5v * 3) 42 + -9v = (-30 + -15v) Solving 42 + -9v = -30 + -15v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '15v' to each side of the equation. 42 + -9v + 15v = -30 + -15v + 15v Combine like terms: -9v + 15v = 6v 42 + 6v = -30 + -15v + 15v Combine like terms: -15v + 15v = 0 42 + 6v = -30 + 0 42 + 6v = -30 Add '-42' to each side of the equation. 42 + -42 + 6v = -30 + -42 Combine like terms: 42 + -42 = 0 0 + 6v = -30 + -42 6v = -30 + -42 Combine like terms: -30 + -42 = -72 6v = -72 Divide each side by '6'. v = -12 Simplifying v = -12
| 3-2x^2=11 | | 3x+18=10x-20 | | 12x+6=-15x+75 | | -38+9t-(-14t)=54 | | 5x^2-16x-9=0 | | -6(a+1)=-18+6a | | 2-5z=7z-9-2 | | 111=6x+6x+3 | | 12m-5m-2= | | 5t^2-t-6=0 | | 12m=60 | | 27=9q | | -224=-7(-7n-8)-9n | | 6x+36=12x-3 | | 5x+6+7x=138 | | -7+2.5x=19-4x | | 4n+6n=30 | | 790=395w | | -6x^2+54x+132=0 | | 3x^2=x+5 | | 20=2t+4 | | 6(4b+8)=24 | | 0.20(15-x)=x^2 | | 20z^2+5pz^2-8x-2px= | | 3n^2-10n+7=0 | | 4n+(-6)=14 | | -8x+8(4-x)=-48 | | 2a+14=20 | | 15-5m^2-3r^2+m^2r^2= | | 3n-16=41 | | 36=4x+7x+3 | | c^2-11c+30=0 |